(untitled) (The Research of Medical Science Review, 2025)
Background Cardiovascular diseases (CVD) constitute a major global health burden, with its progression closely related to dyslipidemia and atherosclerosis. The lack of specific therapeutic interventions to target the CVD at several phases leads to challenges for effective treatment. However, lipid-lowering medications contribute substantially to cardiovascular health but still, there is a debate about their precise effect on CVD outcomes. Proprotein convertase subtilisin/kexin type 9 (PCSK9) is a liver secretary enzyme that modulates the density of LDL receptors (LDLR) on hepatocyte surface and regulates plasma level of low-density lipoprotein cholesterol (LDL-C). Studies have confirmed that PCSK9 inhibitors with remarkable lipid-lowering effects and clinical efficacy substantiate the need for further research for their additional role in the managing cardiovascular diseases. Purpose This review aims to explore the mechanism and relationship between lipid metabolism, cardiovascular diseases, and PCSK9. Moreover, it also assesses the effects of natural PCSK9 inhibitors in managing cardiovascular health conditions and offers updated therapeutic protocol guidance. Method Using multiple electronic databases such as PubMed, Scopus, Google Scholar, and Science Direct, covering studies from 2013 to 2023, a comprehensive literature search was conducted. Keywords such as PCSK9 inhibitors, dyslipidemia, cardiovascular diseases, medicinal plants, and natural PCSK9 inhibitors in vitro and in vivo were employed. Results PCSK9 plays a substantial role in lipid regulation through both LDLR-dependent and independent pathways influencing cardiovascular health. Clinical studies revealed a positive relation between increased PCSK9 levels and CVD severity showing positive implications for lipid regulation. PCSK9 inhibitors are shown to be effective in decreasing LDL-C levels and improving lipid profiles, which may decrease the progression of atherosclerosis. In vivo studies also exhibited the potential of PCSK9 inhibitors to reduce cardiovascular diseases. Moreover, medicinal plants and compounds such as berberine, curcumin, resveratrol, quercetin, pinostrobin, eugenol, kaempferol, and other bioactive compounds are recognized as natural PCSK9 inhibitors and show potential cardiovascular benefits. These benefits may occur due to transcriptional inhibition, reduction in secretion, or other pathways. Conclusion PCSK9 plays a crucial part in pathophysiology of cardiovascular diseases and PCSK9 inhibitors have shown promising effects in the management of cardiovascular diseases in clinical and preclinical studies. Medicine plants and bioactive compounds can result in positive cardiovascular outcomes owing to their antioxidant, anti-inflammatory, and PCSK9 inhibition properties. PCSK9 inhibition can be employed as an auspicious therapeutic strategy for cardiovascular disease.